Social issues in science and technology : an encyclopedia - Newton, David E. (Santa Barbara, Calif. : ABC-CLIO, 1999)
Contains alphabetically arranged entries that explore over one hundred topics in which scientific advances have raised new issues for society, including DNA fingerprinting, euthanasia, needle exchange programs, and organ transplants; and includes illustrations, a bibliography, and an index.
Includes bibliographical references (p. 291-296) and index.
Book Report.
Choice.
Library Journal.
Young Adult
Keywords: Science -- Social aspects -- Encyclopedias; Technology -- Social aspects -- Encyclopedias; Science -- Social aspects -- Encyclopedias; Technology -- Social aspects -- Encyclopedias